Costos económicos y sociales del conflicto en Colombia : ¿cómo construir un posconflicto sostenible? (2014)
Video recomendado: https://www.youtube.com/watch?v=JcNICzUqEDc&list=UU0B5XoeTd110gUIyRpguWvg